Patients with Nonalcoholic Fatty Liver Disease (NAFLD) have Higher Oxidative Stress in Comparison to Chronic Viral Hepatitis - Kumar, Amit (Elsevier, 2013)
INTRODUCTION: Oxidative stress and cytokines play an important role in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). We compared the presence of oxidative stress and cytokines in 25 patients with NAFLD with 25 age, sex and BMI-matched patients with chronic viral hepatitis (CVH) and 25 healthy volunteers (HV). METHODOLOGY: Oxidative stress was studied biochemically by markers of lipid peroxidation and biochemical assessment of anti-oxidant status and various cytokines were studied by ELISA. RESULTS: Patients with NAFLD had significantly higher levels of malondialdehyde (MDA) (p = 0.000) and conjugated dienes (CD) (p = 0.000) in comparison to HVs. Patients with NAFLD also had significantly higher MDA levels (p = 0.000) in comparison to CVH patients. Patients with NAFLD had significantly lower GSH levels (p = 0.004) in comparison to HVs. Patients with NAFLD had higher GPx activity (p = 0.028) in comparison to HVs. Catalase activity was significantly decreased in both NAFLD (p = 0.001) and CVH patients (p = 0.000) in comparison to HVs. Patients with NAFLD had significantly higher SOD activity (p = 0.000) in comparison to CVH patients. There was no difference in serum levels of IL-1β and TNF-α amongst three groups. Patients with CVH were found to have higher IL-8 serum levels (p = 0.039) in comparison to HVs. CVH patients also had higher TGF-β levels (p = 0.002) in comparison to both NAFLD patients and HVs. CONCLUSION: Differences in the markers of oxidative stress and anti-oxidant status between NAFLD, CVH and healthy volunteers suggest presence of higher oxidative stress in patients with NAFLD.